Illocutionary Act of Balinese Song Lyrics: Types and Function in Pandemic Era - Dian Puspita Candra, Komang (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This study aims to discover the types and the function of illocutionary act used in Balinese song lyrics. The data source of this study was taken from one of the famous Balinese singers in Bali namely Ray Peni. This study limit the data source only using 5 songs with a pandemic theme entitled Gering Agung, Dagang Canang Sing Ngabe Bunga, Sandal Anyud, Nyantos Dewa Nyekala and Curhatan TKI . The data were collected used observation method and note taking technique. All of the data were analyzed qualitatively by using the theory from Searle (1969) and Leech (1983) about the types and also function of illocutionary act. The findings show that four types of illocutionary act found in the song lyric, those are assertive, directive, exspresive and declarative. Moreover, four function of illocutionary act found in the song lyric, they are collaborative, competitive, convivial and conflictive. Directive and assertive illocutionary act become the dominant types of illocutionary act occurred in song lyrics with pandemic theme. Collaborative function occurred in assertive and directive illocutionary act. Directive illocutionary act also has competitive function. Expressive illocutionary act has convivial and conflictive function. Declarative illocutionary act only has conflictive function